2001
DOI: 10.1101/gad.896201
|View full text |Cite
|
Sign up to set email alerts
|

Terminal proteins essential for the replication of linear plasmids and chromosomes in Streptomyces

Abstract: Linear plasmids and chromosomes of the bacterial genus Streptomyces have proteins of unknown characteristics and function linked covalently to their 5 DNA termini. We purified protein attached to the end of the pSLA2 linear plasmid of Streptomyces rochei, determined the N-terminal amino acid sequence, and used this information to clone corresponding genes from a S. rochei cosmid library. Three separate terminal protein genes (here designated as tpgR1, tpgR2, and tpgR3), which map to the S. rochei chromosome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 65 publications
3
127
0
1
Order By: Relevance
“…Eventually, the complete nucleotide sequence (356 023 bp) of SCP1 was determined, 17 which confirmed the size of TIRs (75 122 bp) and located the mmy gene cluster, a replication origin, two partition genes (parA and parB) and others. However, a terminal protein gene (tpg) 18 was not identified from the sequence data, because of the unique telomere sequence of SCP1. Later, Huang et al 19 isolated the terminal protein as a complex with SCP1 and finally identified the tpc (terminal protein of SCP1, orf127) and tac (telomere-associated protein of SCP1, orf125) genes of SCP1.…”
Section: Giant Linear Plasmids In Streptomycesmentioning
confidence: 99%
“…Eventually, the complete nucleotide sequence (356 023 bp) of SCP1 was determined, 17 which confirmed the size of TIRs (75 122 bp) and located the mmy gene cluster, a replication origin, two partition genes (parA and parB) and others. However, a terminal protein gene (tpg) 18 was not identified from the sequence data, because of the unique telomere sequence of SCP1. Later, Huang et al 19 isolated the terminal protein as a complex with SCP1 and finally identified the tpc (terminal protein of SCP1, orf127) and tac (telomere-associated protein of SCP1, orf125) genes of SCP1.…”
Section: Giant Linear Plasmids In Streptomycesmentioning
confidence: 99%
“…This protein falls into the class of TPs that include TpgR1, TpgR2 and Tpgr3 from S. rochei, TpgL from S. lividans, TpgC from S. coelicolor and TpgSLP2 from the 50 kb linear plasmid SCP2 of S. lividans (Bao & Cohen, 2001Yang et al, 2002). The tpgR1 gene mapped to the S. rochei chromosome and the tpgR2 and tpgr3 genes mapped to the 206 kb and 100 kb linear plasmids within S. rochei (Bao & Cohen, 2001). The TP homologue TpgSV2, identified on pSLV45, is most probably also involved in protein-primed DNA synthesis for plasmid replication.…”
Section: Sequence Analysis and Deduced Functions Of Pslv45 Proteinsmentioning
confidence: 99%
“…SLV.25, designated tpgSV45, encodes a putative protein of 185 aa with very strong similarity (52 % identity, 62 % positives), over its entire length, to TpgR2, a recently described 59 terminal binding protein from S. rochei (Bao & Cohen, 2001). This protein falls into the class of TPs that include TpgR1, TpgR2 and Tpgr3 from S. rochei, TpgL from S. lividans, TpgC from S. coelicolor and TpgSLP2 from the 50 kb linear plasmid SCP2 of S. lividans (Bao & Cohen, 2001Yang et al, 2002). The tpgR1 gene mapped to the S. rochei chromosome and the tpgR2 and tpgr3 genes mapped to the 206 kb and 100 kb linear plasmids within S. rochei (Bao & Cohen, 2001).…”
Section: Sequence Analysis and Deduced Functions Of Pslv45 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their 'telomeres' contain inverted repeat sequences from 44 to 180 kb long Pandza et al, 1998). The 39 telomeric ends are free, but the 59 telomeric ends are blocked by covalently linked telomere terminal proteins (Bao & Cohen, 2001;Yang et al, 2002). Many Streptomyces linear plasmids have conserved telomeric sequences (e.g.…”
Section: Introductionmentioning
confidence: 99%